Soybean Maturity Groups, Environments, and Their Interaction Define Mega-environments for Seed Composition in Argentina - Dardanelli, Julio Luis (2006)
Argentina is the largest soybean [Glycine max (L.) Merrill] meal and oil exporter in the world, with crops covering a 23° to 39° S latitude range, allowing the presence of genotypes from different maturity groups (MG). Multi-environment yield trials (MET) for commercial cultivars are conducted each year across the crop area. The aim of this paper was to evaluate the consistency of MG effects and its interaction with environments (E), first to investigate if different mega-environments (ME) for oil, protein, and oil + protein exist in Argentina, and second to identify superior MG regarding these traits. We analyzed a 3-yr series of oil and protein data from MET involving six MG and more than 14 E per year. Statistical analysis was based on ANOVA and graphical displays from E-centered biplots to explore MG-related effects and to identify ME. No ME were identified for oil content because of MG II, III, and IV showed higher content than other groups in every E. Two or three ME (depending on the growing season) were identified for protein and oil + protein contents; in one of them MG VI cultivars had the highest value of these compounds whereas in the other set of E, higher yielding cultivars were from MG II–III. The oil variations among E depended mainly on MG effects suggesting broad adaptations of short MG, whereas MG × E interaction effects for protein and oil + protein were higher than for oil, and enough to create opportunities for handling environment-specific adaptations.